Implementation of TQM Based Human Resources Management Development - Lilis Wati (IAIN Salatiga, 2022)
AbstractThis paper presents the development of human resources based on total quality management carried out at MIN 1 Nagan Raya Aceh. Total quality management is an approach offered so that institutions can survive and be able to win the competition between existing institutions. This research uses a qualitative case study approach. The data collection technique is done through; observation, interview and documentation. Furthermore, the research data is presented in the form of descriptive narrative. The results showed that; MIN 1 Nagan Raya Aceh implements several stages in human resource management, namely planning, recruiting, and developing human resources which are carried out in a planned, systematic and quality-oriented manner on an ongoing basis. Through the implementation of human resource development based on total quality management,